DNA-binding studies of a series of novel water-soluble derivatives of 1,4-dihydropyridine - Leonova, E.; Rostoka, E.; Baumane, L.; Borisovs, V.; Smelovs, E.; Bisenieks, I.; Brūvere, I.; Bisenieks, E.; Duburs, G.; Sjakste, N. (Вiopolymers and Cell, 2018)
Aim. to determine DNA interaction modes for a series of 1,4-dihydropyridines with different biological activities synthesized in the Latvian Institute of Or-ganic Synthesis. Methods. Affinity of the compounds to DNA was detected by UV/VIS spec-trometry and re-proofed by means of spectrofluorimetry, EBr extrusion assay, cyclic voltammetry and DNA melting. Radical scavenging was tested by electron paramagnetic resonance spectros-copy, peroxynitrite binding was monitored spectrophotometrically, protection of DNA against hydroxyl radical was determined by gel electrophoresis. Results. In a series of water-soluble monocyclic derivatives of 1,4-dihydropyridine with carboxylate groups in position-4 the different affinity to DNA was determined mainly by substituents in positions 3 and 5. 1,4-DHP with eth-oxycarbonyl groups in positions 3 and 5 (AV-153) manifested high affinity to DNA. Strong ef-fects were observed in the spectra of tricyclic fused derivatives (PP-150-Na and PP-544-NH4). Unlike AV-153, J-4-96 did not extrude EtBr from the complex with DNA, this indicates binding to minor groove. Ability of PP-544-NH4 to intercalate DNA molecule was proved electrochemi-cally and by DNA melting. No correlation between affinity of a 1,4‑DHP to DNA and capabili-ties of the compound to bind peroxynitrite, to scavenge hydroxyl radical or to protect DNA against the above radical were observed. Discussion. DNA-binding activities of 1,4-DHP are evi-dently determined by groups in positions 3 and 5. Tricyclic fused 1,4-DHP derivatives are also good DNA binders. Ability to interact with DNA does not correlate with other effects produced by the compounds.